2016
DOI: 10.15376/biores.11.4.10087-10098
|View full text |Cite
|
Sign up to set email alerts
|

Solar Torrefaction of Solid Olive Mill Residue

Abstract: Torrefaction is a thermochemical pretreatment method for improving fuel characteristics of biomass. The process is conducted between 200 and 300 °C under inert atmosphere. The relatively low process temperature of torrefaction makes the use of solar energy suitable with low costs. In this study, solid olive mill residue (SOMR) was used to test the feasibility of using solar energy in the torrefaction process. SOMR is an agricultural waste obtained from olive oil extraction, and it is mainly produced in the Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Study concluded that the optimum conditions for the torrefaction of olive waste would be temperature of 280°C and residence time of 30 min [36]. In another study Cellatoglu and Ilkan assessed torrefaction of olive waste in a novel type of reactor using solar energy, concentrated by a parabolic dish, to deliver the heat for the process [37]. The study demonstrated that solar energy can be stored in a solid fuel, by being used as a source of the process heat [37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Study concluded that the optimum conditions for the torrefaction of olive waste would be temperature of 280°C and residence time of 30 min [36]. In another study Cellatoglu and Ilkan assessed torrefaction of olive waste in a novel type of reactor using solar energy, concentrated by a parabolic dish, to deliver the heat for the process [37]. The study demonstrated that solar energy can be stored in a solid fuel, by being used as a source of the process heat [37].…”
Section: Introductionmentioning
confidence: 99%
“…In another study Cellatoglu and Ilkan assessed torrefaction of olive waste in a novel type of reactor using solar energy, concentrated by a parabolic dish, to deliver the heat for the process [37]. The study demonstrated that solar energy can be stored in a solid fuel, by being used as a source of the process heat [37]. This would enable the use of torgas for other purposes such as biorefinery feedstock.…”
Section: Introductionmentioning
confidence: 99%
“…The equipment used was a drying oven, china crucible of 32cc volume, electronic micro balance and desiccators following the ASTM-E871. The MC of the samples was determined by (1) [16]:…”
Section: Characteristic and Energy Content Of Sugarcane Trashmentioning
confidence: 99%
“…The equipment used was chromium-nickel crucible with lid and an electrically operated electric furnace. The VM content of the samples was determined by (2) [16]:…”
Section: Characteristic and Energy Content Of Sugarcane Trashmentioning
confidence: 99%